Performance enhancement of wind-driven standalone PMSG integrated with battery storage system verification. Issue 2 (2nd April 2020) - Elmorshedy, Mahmoud F.; Allam, Said M.; Rashad, Essam M.
ABSTRACT: Integrating renewable energy sources (RES) with energy storage systems (ESSs) has become an efficient solution to supply sustained electrical power to isolated loads with better quality. An improvement verification of a standalone wind-driven generator system (WDGS) integrated with a battery storage system (BSS) is presented in this paper. An enhanced maximum power point tracking technique (MPPTT) used for WPGS is presented first. Then, operation of the battery is moderated using a battery control unit which supervises the different modes of operation and ensures a constant dc-bus voltage under different circumstances such as variable wind speed and loading events. Thirdly, a variable modulation index technique is suggested for load voltage regulation in terms of both rms and frequency. Finally, a control strategy for managing the power flow is suggested with an examination based on both generated and consumed powers and the BSS state-of-charge (SOC). An experimental setup has been established to investigate the effectiveness of the proposed control approach during several circumstances. Comprehensive simulation and experimental proofs have demonstrated the competence of developed management strategy to extract the maximum power along with a steady load voltage and frequency (V&f).